Perception of fast time fluctuations in the sound level by persons with a cochlear implant - Rafał KWIATKOWSKI; Edward HOJAN; Witold SZYFTER; Anna FURMANN; Dorota HOJAN-JEZIERSKA (Archives of Acoustics)
The paper presents results of scaling of loudness changes of natural sounds for persons with a cochlear implant by the so-called NSLE method. The possibilities of the use of this method of loudness scaling of natural sounds in the rehabilitation of persons with a cochlear implant have been analysed.